Durable composite diaphragm material and preparation method thereof
By adopting a multi-layer structure diaphragm material, combined with a corrosion-resistant layer, a silicone rubber intermediate layer and an ethyl acrylate polymer elastic layer, the problem of insufficient durability of the existing diaphragm material rubber layer is solved, and higher durability and mechanical strength are achieved, extending the service life of the diaphragm and reducing production safety risks.
Patent Information
- Application Number
- CN202411893528.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
AI Technical Summary
In the diaphragm materials of existing diaphragm pumps, the rubber layer has insufficient durability and is prone to breaking, resulting in insufficient resilience of the diaphragm, which may cause fluid leakage, affect production progress and pose a threat to production safety.
The separator material with a multi-layer structure, including a corrosion-resistant layer, a silicone rubber intermediate layer and an ethyl acrylate polymer elastic layer, improves the fatigue threshold and flexibility of the rubber layer by modifying the composite of silicone rubber and fluoroplastic.
It significantly improves the durability and mechanical strength of the diaphragm material, extends the service life of the diaphragm, and avoids fluid leakage and production safety risks.
Smart Images

Figure BDA0005201179480000091 
Figure BDA0005201179480000101
Abstract
Description
Technical Field
[0001] The present application relates to a durable composite diaphragm material and a preparation method thereof, belonging to the technical field of diaphragm pump materials. Background Art
[0002] Diaphragm pumps are pumps that achieve fluid flow through the reciprocating motion of a diaphragm. Diaphragm pumps have good self-priming capabilities and can handle high-viscosity liquids. They can operate without fluid without damage and are widely used in semiconductors, chemicals, pharmaceuticals, food processing, sewage treatment, mining, and many other industrial fields. The design and operation of diaphragm pumps make them a versatile and reliable fluid handling equipment, especially suitable for applications that have special requirements for the sealing and safety of the pump.
[0003] However, the core performance of the diaphragm pump is also restricted by the elastic diaphragm component: the common material of the diaphragm of the existing diaphragm pump is a composite of fluoroplastics and rubber. The rubber layer in the diaphragm composite material is prone to insufficient durability. The rupture of the rubber layer will cause the overall resilience of the diaphragm to be insufficient and even generate instantaneous impact force at the moment of rupture, causing damage to the fluoroplastic and causing fluid leakage. Problems, affecting production progress and posing a threat to production safety, therefore, there is an urgent need for a highly durable diaphragm material. Summary of the invention
[0004] In order to solve the above problems, the present application proposes a durable composite diaphragm material and a preparation method thereof. By limiting the diaphragm material to a multi-layer structure and the materials of each layer of the diaphragm material, the fatigue threshold and flexibility resistance of the rubber back membrane are improved, making the diaphragm material have higher durability.
[0005] According to one aspect of the present application, a durable composite diaphragm material is provided, comprising:
[0006] A corrosion-resistant layer, wherein the corrosion-resistant layer is fluoroplastic;
[0007] A back film, the back film comprising an intermediate layer and an elastic layer;
[0008] The middle layer is made of silicone rubber material, and the elastic layer is made of ethyl acrylate polymer;
[0009] The corrosion-resistant layer, the intermediate layer and the elastic layer are compounded in sequence.
[0010] The corrosion-resistant layer can provide protection for the back film in strong acids, alkalis and organic solvents to prevent it from being corroded or penetrated; the intermediate layer can promote good compounding between the corrosion-resistant layer and the elastic layer and improve the strength of the back film; the elastic layer provides good flexibility and resilience.
[0011] Optionally, the silicone rubber material is prepared from the following components in parts by weight: 60 to 70 parts of methyl divinyl silicone rubber, 20 to 40 parts of white carbon black, 1 to 2.5 parts of silane coupling agent, 0.2 to 1.5 parts of vulcanizing agent, and 0.2 to 1.2 parts of catalyst.
[0012] Silica gel can not only improve the fatigue resistance of silicone rubber, but also improve the strength and toughness of silicone rubber; silane coupling agent can make the distribution of silica gel in silicone rubber better, thereby improving the performance of silica gel and silicone rubber.
[0013] Specifically, the silane coupling agent is at least one of hydroxy silicone oil, hexamethyldisilazane, vinyltriethoxysilane or γ-mercaptopropyltriethoxysilane; the vulcanizing agent is at least one of benzoyl peroxide, diisopropylbenzene peroxide, 2,4-dichlorobenzoyl peroxide, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane peroxide; and the catalyst is chloroplatinic acid.
[0014] Optionally, the silicone rubber material further comprises 5 to 10 parts of ethyl acrylate monomer, so as to obtain better composite performance.
[0015] Optionally, the elastic layer is prepared from the following components in parts by weight: 15 to 20 parts of ethyl acrylate monomer, 1 to 2 parts of crosslinking agent, 1 to 6 parts of photoinitiator, 50 to 70 parts of solvent, and 8 to 15 parts of silica nanoparticles.
[0016] Ethyl acrylate monomers form single polymer chains and the molecular chains are intertwined with each other; polyethyl acrylate and silica nanoparticles are connected to each other by strong bonds to form a polymer network; when impacted by external force, the impact force is transmitted and dissipated between the rigid nanoparticles and the polymer with extremely small friction between each other, thereby increasing the fatigue threshold of the elastomer; in addition, the dispersion and penetration of nanoparticles in the high molecular polymer also increase the elastic modulus of the material, thereby reducing the risk of rupture of the elastomer of the diaphragm material and extending the service life of the diaphragm.
[0017] Specifically, the crosslinking agent is a tricyclodecane acrylate containing two CC double bonds (tricyclo[5.2.1.02,6]decane dimethanol diacrylate, tricyclodecane dimethanol dimethacrylate); the photoinitiator is a cleavage-type photoinitiator, including at least one of 1-hydroxy-cyclohexyl-phenyl ketone, 2-hydroxy-2-methylpropiophenone, and 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone; and the solvent is N,N-dimethylformamide.
[0018] Optionally, the silicon dioxide nanoparticles are silicon dioxide nanoparticles modified by 3-(isomethacryloyloxy)propyltrimethoxysilane and propyltriethoxysilane, respectively, and the mass ratio of the two silicon dioxide nanoparticles is 1:(1.2-1.5).
[0019] 3-(Isobutylacryloyloxy)propyltrimethoxysilane-modified silica nanoparticles have adhesive properties and can be dispersed in clusters in high molecular weight polymers, which is beneficial to the transmission of force but will affect the uniformity of the elastic layer; propyltriethoxysilane-modified silica nanoparticles have non-adhesive properties and can be evenly dispersed in the polymer. Limiting the ratio of the two is beneficial to retaining the anti-fatigue effect of the sticky modified nanoparticles, preventing the problem of poor uniformity caused by agglomerates, and improving the mechanical properties of the elastic layer.
[0020] Optionally, the corrosion-resistant layer is modified by plasma on a side in contact with the intermediate layer.
[0021] The reinforcing layer is modified by plasma on the side in contact with the intermediate layer.
[0022] A large number of free radicals are generated on the surface of plasma-modified fluoroplastics, which can obtain better affinity through reaction with organic matter, thereby improving the composite performance of fluoroplastics and other materials; plasma modification only affects the surface properties of the material, and therefore will not affect the properties of the reinforcement layer material itself.
[0023] The middle layer is based on silicone rubber and can be compounded with plasma-modified fluoroplastics to achieve better bonding between the reinforcing layer and the elastomer.
[0024] Optionally, the plasma-modified gas is one of H2, Ar, and He.
[0025] The gases are all capable of efficiently modifying fluoroplastics.
[0026] Optionally, the corrosion-resistant layer is modified by plasma and then grafted by acrylic acid immersion.
[0027] Acrylic acid impregnated grafted fluoroplastics have stronger affinity with modified silicone rubber and achieve better composite effects.
[0028] According to another aspect of the present application, a method for preparing a durable composite diaphragm material is provided, which is used to prepare the durable composite diaphragm material, comprising the following steps:
[0029] (1) Molding and sintering fluoroplastic powder to obtain a corrosion-resistant layer;
[0030] (2) After fully mixing methyl divinyl silicone rubber, white carbon black and silane coupling agent, adding vulcanizing agent and catalyst, mixing evenly, pouring into a mold and vulcanizing at room temperature to obtain modified silicone rubber;
[0031] (3) adding ethyl acrylate monomer and silica nanoparticles to the solution, stirring and ultrasonically treating, then adding a crosslinking agent and a photoinitiator, stirring, pouring into a mold, and curing under UV light in a nitrogen atmosphere to obtain an elastic layer;
[0032] (4) The intermediate layer, the corrosion-resistant layer and the elastic layer are bonded and compounded with an acrylic adhesive to obtain a durable composite diaphragm material, wherein the thickness of the composite diaphragm material is 4.5 to 7 mm.
[0033] Specifically, the molding pressure in step (1) is 20-30 MPa, the sintering temperature is 350-380° C., and the thickness of the obtained corrosion-resistant layer is 1.5-3 mm.
[0034] Specifically, the light intensity of the UV lamp curing in step (3) is 1.5 mW / cm 2 , the lighting time is 10 to 15 hours.
[0035] Optionally, the method further comprises, after obtaining the corrosion-resistant layer, subjecting one side of the corrosion-resistant layer to plasma surface treatment, and subjecting the layer to immersion grafting treatment in a 35% acrylic acid solution.
[0036] Specifically, the plasma surface treatment process is to react for 20 to 40 seconds at room temperature and in a 15 to 50 Pa gas atmosphere, and the discharge power of the discharge power source is 80 to 120W.
[0037] Optionally, the adhesive is acrylate.
[0038] The beneficial effects of this application include but are not limited to:
[0039] 1. The durable composite diaphragm material provided in the present application, by providing a corrosion-resistant layer and a back film composed of an intermediate layer and an elastic layer, makes the diaphragm material not only have strong corrosion resistance and high resilience, but also have high mechanical strength and fatigue resistance.
[0040] 2. The durable composite diaphragm material provided in the present application has a modified silicone rubber as an intermediate layer, and is composited with a surface-modified corrosion-resistant layer and an elastic layer on both sides, thereby improving the overall compositeness of the material and making it less likely to have interlayer separation. At the same time, the plasma-modified and grafted fluoroplastic and the silicone rubber with added ethyl acrylate monomer are combined with an acrylic adhesive to have significant composite properties, and the composite diaphragm material has excellent integrity without the problem of interlayer separation.
[0041] 3. The durable composite diaphragm material provided in the present application is modified by a silicone rubber intermediate layer and an elastomeric filler, so that when the diaphragm material is subjected to impact force, the impact force is fully dispersed due to the structural characteristics between molecules, thereby greatly improving the fatigue threshold and impact resistance of the back membrane and improving the durability of the diaphragm material. DETAILED DESCRIPTION
[0042] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0043] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in this patent are for demonstration purposes only.
[0044] Example 1
[0045] The method for preparing the durable composite diaphragm material comprises the following steps:
[0046] (1) 100 parts of fluoroplastic powder were molded at 30 MPa and sintered at 250°C to obtain a corrosion-resistant layer with a corrosion-resistant thickness of 2 mm;
[0047] (2) After 70 parts of methyl divinyl silicone rubber, 40 parts of white carbon black, and 2.5 parts of hexamethyldisilazane are fully mixed, 1.5 parts of dicumyl peroxide and 1.2 parts of chloroplatinic acid are added, the mixture is evenly poured into a mold, and vulcanized at room temperature to obtain a modified silicone rubber;
[0048] (3) 15 parts of ethyl acrylate monomer and 15 parts of silica nanoparticles were added to 70 parts of N,N-dimethylformamide, stirred and ultrasonically treated, and then 2 parts of tricyclodecane dimethanol dimethacrylate and 6 parts of 2-hydroxy-2-methylpropiophenone were added, stirred and poured into a mold. Under a nitrogen atmosphere, the mixture was heated at 1.5 mW / cm 2 The light intensity is UV lamp irradiation and curing for 15 h to obtain an elastic layer;
[0049] (4) The middle layer, the corrosion-resistant layer and the elastic layer are bonded and compounded with acrylic ester to obtain a durable composite diaphragm material 1# with a thickness of 5 mm.
[0050] Example 2
[0051] The method for preparing the durable composite diaphragm material comprises the following steps:
[0052] (1) 100 parts of fluoroplastic powder were molded at 20 MPa and sintered at 350°C to obtain a corrosion-resistant layer with a corrosion-resistant thickness of 2 mm;
[0053] (2) After 60 parts of methyl divinyl silicone rubber, 20 parts of white carbon black and 1 part of hexamethyldisilazane are fully mixed, 0.2 parts of dicumyl peroxide and 0.2 parts of chloroplatinic acid are added, the mixture is evenly poured into a mold and vulcanized at room temperature to obtain a modified silicone rubber;
[0054] (3) 15 parts of ethyl acrylate monomer and 8 parts of silica nanoparticles were added to 50 parts of N,N-dimethylformamide, stirred and ultrasonically treated, and then 1 part of tricyclodecane dimethanol dimethacrylate and 1 part of 2-hydroxy-2-methylpropiophenone were added, stirred and poured into a mold. Under a nitrogen atmosphere, the mixture was heated at 1.5 mW / cm 2 The light intensity is UV lamp irradiation and curing for 10 h to obtain an elastic layer;
[0055] (4) The middle layer, the corrosion-resistant layer and the elastic layer are bonded and compounded with acrylic ester to obtain a durable composite diaphragm material 2# with a thickness of 5 mm.
[0056] Example 3
[0057] The method for preparing the durable composite diaphragm material comprises the following steps:
[0058] (1) 100 parts of fluoroplastic powder were molded at 25 MPa and sintered at 300°C to obtain a corrosion-resistant layer with a corrosion-resistant thickness of 2 mm;
[0059] (2) Plasma surface treatment was performed on one side of the corrosion-resistant layer in a 50 Pa He atmosphere for 30 seconds with a discharge power of 100 W, and then the surface was immersed in a 35% acrylic acid solution for grafting treatment;
[0060] (3) After 70 parts of methyl divinyl silicone rubber, 20 parts of white carbon black and 2 parts of hexamethyldisilazane are fully mixed, 1 part of dicumyl peroxide and 0.8 parts of chloroplatinic acid are added, the mixture is evenly poured into a mold and vulcanized at room temperature to obtain a modified silicone rubber;
[0061] (4) 20 parts of ethyl acrylate monomer and 10 parts of silica nanoparticles were added to 60 parts of N,N-dimethylformamide, stirred and ultrasonically treated, and then 1.5 parts of tricyclodecane dimethanol dimethacrylate and 4 parts of 2-hydroxy-2-methylpropiophenone were added, stirred and poured into a mold. Under a nitrogen atmosphere, the mixture was heated at 1.5 mW / cm 2 The light intensity is UV lamp irradiation and curing for 12 h to obtain an elastic layer;
[0062] (5) The middle layer, the corrosion-resistant layer and the elastic layer are bonded and compounded with acrylic ester to obtain a durable composite diaphragm material 3# with a thickness of 5 mm.
[0063] Example 4
[0064] The difference from Example 3 is that the silicone rubber further includes 5 parts of ethyl acrylate monomer to prepare a durable composite diaphragm material 4#.
[0065] Example 5
[0066] The difference from Example 3 is that the silicon dioxide nanoparticles in the elastic layer are replaced with modified nanoparticles modified with 3-(isomethacryloyloxy)propyltrimethoxysilane and propyltriethoxysilane (1:1.2) to prepare a durable composite diaphragm material 5#.
[0067] Example 6
[0068] The difference from Example 3 is that the silicon dioxide nanoparticles in the elastic layer are replaced with modified nanoparticles modified with 3-(isomethacryloyloxy)propyltrimethoxysilane and propyltriethoxysilane (1:1.5) to prepare a durable composite diaphragm material 6#.
[0069] Example 7
[0070] The difference from Example 3 is that the silicon dioxide nanoparticles in the elastic layer are replaced with modified nanoparticles modified with 3-(isomethacryloyloxy)propyltrimethoxysilane to prepare a durable composite diaphragm material 7#.
[0071] Example 8
[0072] The difference from Example 3 is that the silicon dioxide nanoparticles in the elastic layer are replaced with modified nanoparticles modified with propyltriethoxysilane to prepare a durable composite diaphragm material 8#.
[0073] Example 9
[0074] The difference from Example 3 is that the white carbon black filler in the silicone rubber is replaced with an organic montmorillonite filler to prepare a durable composite diaphragm material 9#.
[0075] Example 10
[0076] The difference from Example 3 is that 10 parts of silicon dioxide nanoparticles are replaced by 20 parts to prepare a durable composite diaphragm material 10#.
[0077] Embodiment 11
[0078] The difference from Example 3 is that one side of the corrosion-resistant layer is plasma modified in an acrylic acid gas atmosphere to prepare a durable composite diaphragm material 11#.
[0079] Comparative Example 1
[0080] The difference from Example 3 is that no silicone rubber layer is provided, and the elastic layer is compounded with the corrosion-resistant layer to obtain a durable composite diaphragm material D1# with a thickness of 5 mm.
[0081] Comparative Example 2
[0082] The difference from Example 3 is that the silicone rubber layer is replaced by a natural rubber layer, and the elastic layer is compounded with the corrosion-resistant layer to obtain a durable composite diaphragm material D2# with a thickness of 5 mm.
[0083] Experimental example
[0084] The various properties of the diaphragm pump diaphragms provided in the embodiments and comparative examples of the present invention were tested. The elongation at break and the tensile strength were tested according to GB / T 1040.1-2018, the flexural test was tested according to GB / T 41937-2022, and the shear strength was tested according to GB / T33334-2016. The test results of the various properties of the embodiments and comparative examples are shown in Table 1:
[0085] Table 1
[0086]
[0087]
[0088] It can be seen from the above data that the composite diaphragm material obtained in this scheme has excellent tensile shear strength and bending number performance, which shows that the diaphragm material obtained in this scheme has strong durability and improved impact resistance.
[0089] Each embodiment in this specification is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0090] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A durable composite diaphragm material, characterized in that: include: A corrosion-resistant layer, wherein the corrosion-resistant layer is fluoroplastic; A back film, the back film comprising an intermediate layer and an elastic layer; The middle layer is made of silicone rubber material, and the elastic layer is made of ethyl acrylate polymer; The corrosion-resistant layer, the intermediate layer and the elastic layer are compounded in sequence.
2. The durable composite diaphragm material according to claim 1, characterized in that: The silicone rubber material is prepared from the following components in parts by weight: 60 to 70 parts of methyl divinyl silicone rubber, 20 to 40 parts of white carbon black, 1 to 2.5 parts of silane coupling agent, 0.2 to 1.5 parts of vulcanizing agent, and 0.2 to 1.2 parts of catalyst.
3. The durable composite diaphragm material according to claim 1, characterized in that: The elastic layer is prepared from the following components in parts by weight: 15 to 20 parts of ethyl acrylate monomer, 1 to 2 parts of crosslinking agent, 1 to 6 parts of photoinitiator, 50 to 70 parts of solvent, and 8 to 15 parts of silicon dioxide nanoparticles.
4. The durable composite diaphragm material according to claim 3, characterized in that: The silicon dioxide nanoparticles are silicon dioxide nanoparticles modified by 3-(isomethacryloyloxy)propyltrimethoxysilane and propyltriethoxysilane, respectively, and the mass ratio of the two silicon dioxide nanoparticles is 1:(1.2-1.5).
5. The durable composite diaphragm material according to claim 1, characterized in that: The corrosion-resistant layer is modified by plasma on the side in contact with the intermediate layer.
6. The durable composite diaphragm material according to claim 2, characterized in that: The plasma modified gas is one of H2, Ar and He.
7. The durable composite diaphragm material according to claim 2, characterized in that: After the corrosion-resistant layer is modified by plasma, acrylic acid is used for dipping and grafting.
8. A method for preparing a durable composite diaphragm material, used for preparing the durable composite diaphragm material according to claims 1 to 7, characterized in that: The following steps are involved: (1) Molding and sintering fluoroplastic powder to obtain a corrosion-resistant layer; (2) After fully mixing methyl divinyl silicone rubber, white carbon black and silane coupling agent, adding vulcanizing agent and catalyst, mixing evenly, pouring into a mold and vulcanizing at room temperature to obtain modified silicone rubber; (3) adding ethyl acrylate monomer and silica nanoparticles to the solution, stirring and ultrasonically treating, then adding a crosslinking agent and a photoinitiator, stirring, pouring into a mold, and curing under UV light in a nitrogen atmosphere to obtain an elastic layer; (4) The intermediate layer is bonded to the corrosion-resistant layer and the elastic layer with an adhesive to obtain a durable composite diaphragm material.
9. The method for preparing a durable composite diaphragm material according to claim 8, characterized in that: The method also includes subjecting one side of the obtained corrosion-resistant layer to plasma surface treatment and then subjecting it to immersion grafting treatment in a 35% acrylic acid solution.
10. The method for preparing a composite diaphragm material according to claim 8, characterized in that: The adhesive is acrylate.
Citation Information
Patent Citations
Diaphragm and pump for gas or liquid transportation using same
CN101175935A
Diaphragm of diaphragm pump
CN210799305U